Associations between body weight trajectories and neurodevelopment outcomes at 24 months corrected age in very-low-birth-weight preterm infants: a group-based trajectory modelling study - Wang, Ts-Ting; Chen, Yen-Ju; Su, Yi-Han; Yang, Yun-Hsiang; Chu, Wei-Ying; Lin, Wei-Ting; Chang, Yu-Shan; Lin, Yung-Chieh; Lin, Chyi-Her; Lin, Yuh-Jyh; , Taiwan Premature Infant Follow-up Network (Frontiers in Pediatrics, 2024)
This study aimed to explore the relationship between the trajectories of body weight (BW) zscores at birth, discharge, and 6 months corrected age (CA) and neurodevelopmental outcomes, as well as scores on the Bayley Scales of Infant Development-III (BSID-III) at 24 months CA. Conducted as a population-based retrospective cohort study across 21 hospitals in Taiwan, we recruited 3,334 very-low-birth-weight (VLBW) infants born between 2012 and 2017 at 23-32 weeks of gestation. The main outcomes were instances of neurodevelopmental impairment (NDI), which were defined by the presence of at least one of the following criteria at 24 months CA: cerebral palsy, severe hearing loss, profound vision impairment, or cognitive impairment. The BSID-III was employed to assess neurodevelopment, including cognitive, language, and motor composite scores, at 24 months CA. The analysis, through group-based trajectory modeling, identified three distinct trajectory groups: high-climbing, mid-declining, and low-declining. Using multivariable logistic regression, the study found significant associations between neurodevelopmental impairments and both cystic periventricular leukomalacia (cPVL) (with an adjusted odds ratio [aOR] of 3.59; p < 0.001) and belonging to the low-declining group (aOR: 2.59; p < 0.001). In conclusion, the study demonstrated that a low-declining pattern in body weight trajectory from birth to 6 months CA, along with cPVL, was associated with neurodevelopmental impairments at 24 months CA, and highlighted the importance of early weight trajectory and specific health conditions in predicting later neurodevelopmental outcomes in VLBW infants.